RESPON PERTUMBUHAN AKSESI KEMANGI PADA BERBAGAI KOMPOSISI PUPUK NITROGEN ALAMI - Arifah Rahayu; Wini Nahraeni; Nur Rochman; Arif Faturrochman (Universitas Djuanda Bogor, 2019)
Basil is not only useful as a vegetable, but also has many medicinal properties. This encourages thedevelopment of environmentally friendly basil cultivation, through the use of natural fertilizers.This study aims to determine the response of various basil accessions to the composition of sourceN fertilizer derived from cow urine, kipahit (Tithonia) compost and Urea. The study was conductedwith a factorial completely randomized design. The first factor is the accession of basil, namelyKemang, Ciaruten, Cijujug and Gasol. The second factor is the combination of N fertilizer (10levels), namely 100% N-Urea, 100% N- cow urine, 100% N-kipahit, 75% N-Urea + 25% N- cowurine, 75% N-Urea + 25 % N-kipahit, 50% N-Urea + 50% N-urine cow, 50% N-Urea + 50%kipahit, 25% N-Urea + 75% N-cow urine, 25% N-Urea + 75% N - kipahit, 0% N-Urea + 0% Ncow urine + 0% N-kipahit. The dosage of N fertilizer used is 150 kg N ha-1. The results showedthat the accession of basil which showed good growth and production was 'Ciaruten' and 'Gasol'.The application of Urea fertilizer composition with kipahit compost and Urea with cow urineproduces better growth and production compared to the use of Urea fertilizer or organic fertilizerseparately.Keywords: basil, cow urine, kipahit compost